Rhizobium symbiosis improves amino acid and secondary metabolite biosynthesis of tungsten-stressed soybean (Glycine max) - Preiner, Julian; Steccari, Irene; Oburger, Eva; Wienkoop, Stefanie (Frontiers in Plant Science, 2024)
The industrially important transition metal tungsten (W) shares certain chemical properties with the essential plant micronutrient molybdenum and inhibits the activity of molybdoenzymes such as nitrate reductase, impacting plant growth. Furthermore, tungsten appears to interfere with metabolic processes on a much wider scale and to trigger common heavy metal stress response mechanisms. We have previously found evidence that the tungsten stress response of soybeans (Glycine max) grown with symbiotically associated N2-fixing rhizobia (Bradyrhizobium japonicum) differs from that observed in nitrogen fertilized soy plants. This study aimed to investigate how association with symbiotic rhizobia affects the primary and secondary metabolite profiles of tungsten stressed soybean, and whether changes in metabolite composition enhance the plant’s resilience to tungsten. This comprehensive metabolomic and proteomic study presents further evidence that the tungsten-stress response of soybean plants is shaped by associated rhizobia. Symbiotically grown plants (N fix) were able to significantly increase the synthesis of an array of protective compounds such as phenols, polyamines, gluconic acid and amino acids such as proline. This resulted in a higher antioxidant capacity, reduced root to shoot translocation of tungsten, and potentially also in an enhanced resilience of N fix plants compared to non-symbiotic counterparts (N fed). Taken together, our study revealed a symbiosis specific metabolic readjustment in tungsten-stressed soybean plants, and contributes to a deeper understanding of the mechanisms involved in the rhizobium-induced systemic resistance in response to heavy metals.